2015
DOI: 10.1016/j.neurobiolaging.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Greater glucocorticoid receptor activation in hippocampus of aged rats sensitizes microglia

Abstract: Healthy aging individuals are more likely to suffer profound memory impairments following an immune challenge than are younger adults. These challenges produce a brain inflammatory response that is exaggerated with age. Sensitized microglia found in the normal aging brain are responsible for this amplified response, which in turn interferes with processes involved in memory formation. Here, we examine factors that may lead aging to sensitize microglia. Aged rats exhibited higher CORT levels in the hippocampus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 66 publications
3
50
0
Order By: Relevance
“…This well-tested method has proven to be a powerful tool to study basic microglia biology and microglia immunophenotype and/or activation state under pathological conditions. The isolated cell population is not only sufficiently enriched with microglia and macrophages while excluding other cell types such as astrocytes, but these microglia/macrophages also maintain their functional responsiveness after isolation (Barrientos et al, 2015; Frank, Baratta, Sprunger, Watkins, & Maier, 2007; Frank et al, 2006). Consistent with prior studies, our analysis revealed that purity and enrichment efficiency of myeloid cell suspensions yields over 95% CD11b+ cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This well-tested method has proven to be a powerful tool to study basic microglia biology and microglia immunophenotype and/or activation state under pathological conditions. The isolated cell population is not only sufficiently enriched with microglia and macrophages while excluding other cell types such as astrocytes, but these microglia/macrophages also maintain their functional responsiveness after isolation (Barrientos et al, 2015; Frank, Baratta, Sprunger, Watkins, & Maier, 2007; Frank et al, 2006). Consistent with prior studies, our analysis revealed that purity and enrichment efficiency of myeloid cell suspensions yields over 95% CD11b+ cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its classic role as an immunosuppressant, there is increasing evidence demonstrating that corticosterone can prime hippocampal microglia and potentiate the inflammatory response to a subsequent challenge. [55][56][57] For example, Frank et al 55 elegantly showed that when corticosterone was elevated prior to a peripheral immune challenge (LPS), the resulting inflammatory response in the hippocampus was potentiated. In contrast, when corticosterone was elevated after the immune challenge, the neuroinflammatory response was suppressed.…”
Section: Adult Consumption Of a High-fat Diet: A Vulnerability Factormentioning
confidence: 99%
“…This pheno-type represents a progressive shift in the state of micro-glia from quiescent to primed. As we will discuss in more detail in later sections, in the primed state, microglia are skewed toward exaggerated pro-inflammatory immune responses to subsequent challenges, but typically do not exhibit exaggerated responses in the absence of such challenges (Barrientos et al, 2009a, 2010, 2012, 2015b; Frank et al, 2010b), and these exaggerated proinflammatory responses correlate with long-lasting memory deficits (Barrientos et al, 2006, 2009a, 2011, 2012; Abraham et al, 2008; Chen et al, 2008; Abraham and Johnson, 2009b) (See Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Together, these findings prompted our own laboratory to examine whether normal aging-associated elevations in basal GCs might be associated with microglial priming. Although circulating levels of GCs were not elevated by aging, CORT levels within the hippocampus were indeed elevated throughout the light phase (Barrientos et al, 2015b). The dissociation between circulating and brain levels of CORT is thought to be driven by the enzyme 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1).…”
Section: Introductionmentioning
confidence: 99%